Feasibility Study for Implementing Generative Artificial Intelligence in the IT Industry - Saffari, Gholamreza (International journal of industrial engineering and operational research, 2024)
This paper presents a comprehensive feasibility study on implementing generative artificial intelligence (AI) in the industry. The aim of this study is to assess the potential benefits, challenges, and technical requirements associated with the adoption of generative AI systems in industrial settings. The research methodology involves a thorough literature review, followed by the formulation of research questions and hypotheses. A series of analyses and experiments are conducted to evaluate the feasibility of implementing generative AI, leading to significant insights and recommendations for industry stakeholders.